Ima Fine (Integrated Mangrove, Modern City and Fish Culture Zone) in Coastal Areas - Aditia, Dito; Munna, Kamila (International Research & Development for Human Beings (IRDH), 2024)
As a maritime country, quite a few Indonesian citizens live in coastal areas. The aim of this research is to describe the latest and innovative model for developing human resources in coastal areas, along with the stages of implementation. This research uses a descriptive modeling method that combines two techniques, namely Literature Review and Training Need Analysis. IMA FINE (Integrated Mangrove, Modern City and Fish Cultural Zone) is a human resource development model which aims to combine three components in the form of a mangrove conservation area (Mangrove Zone), a modern city in a coastal area that is environmentally friendly (Modern City), and a fisheries cultivation (Fish Cultural Zone). There are eight stages to realizing IMA FINE, namely surveys, social approaches, making and drafting regional regulations, establishing technical implementers, counseling, regional mapping, implementation monitoring and implementation evaluation. The main implementer of this model is the Matalima Group (City, Environment and Mangrove Community) which is integrated with the local government. Through IMA FINE, coastal communities can optimize existing natural resources without damaging the environment. Apart from that, IMA FINE can pave the way for developing the quality of human resources in coastal areas in the future.